INTEGRASI NILAI-NILAI PENDIDIKAN AGAMA DAN KARAKTER DALAM PENINGKTAN MUTU PENDIDIKAN DI INDONESIA - Nelma Elpayuni; Tin Amalia Fitri; Fisman Bedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Religious and character education plays a very important role in the formation of students' personalities. Based on research conducted by the Education Research Centre of the Ministry of Education and Culture, students who receive good religious education tend to show more positive behaviour and are able to interact socially well. This research uses a qualitative approach through the literature study method. Data were collected from various sources, such as scientific journals, government reports and books relevant to the research topic. The integration of religious and character education values in education in Indonesia has a significant positive impact on the quality of education. Although there are various obstacles in its implementation, many schools have successfully implemented this integration and shown improvements in student behaviour and achievement. Research shows that students who receive an education that integrates these values tend to have better academic performance and better character. This positive impact is evident in various case studies, where schools that implement this integration succeed in creating a more conducive and productive learning environment.